Thực trạng và giải pháp thực hiện các quyền sử dụng đất của hộ gia đình, cá nhân trên địa bàn huyện Ký Sơn, Tỉnh Hòa Bình : Luận văn ThS. Địa chính: 60 85 01 03 - Trần, Thị Hòa (ĐHKHTN, 2017)
106 tr. + CD-ROM